2004
DOI: 10.1111/j.0032-0862.2004.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of deoxynivalenol‐ and nivalenol‐producing chemotypes of Fusarium graminearum isolated from wheat crops in England and Wales

Abstract: Fusarium graminearum , one of the causal agents of fusarium head blight (FHB) of wheat in the UK, can be broadly divided into two chemotypes based on the production of the 8-ketotrichothecenes deoxynivalenol (DON) and nivalenol (NIV). DON-producing isolates can be further distinguished on the basis of the predominant acetyl DON derivative that they produce; 3-acetyl DON (3-AcDON) or 15-acetyl DON (15-AcDON). Functional Tri13 and Tri7 are required for the production of NIV and 4-acetyl NIV, respectively, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
102
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 32 publications
8
102
0
2
Order By: Relevance
“…The 3- isolates belonging to population 2 were included in the analysis of aggressiveness, ten of these were included in the growth rate analysis c 17 3-ADON isolates were included in the analysis of aggressiveness, 16 of these were included in the growth rate analysis ADON chemotype also predominated among a small set of FGSC isolates from an earlier collection of Norwegian cereals (Langseth et al 1999(Langseth et al , 2001, and was found in oat and wheat samples collected between 2009 and 2011 in Sweden, whereas the 15-ADON chemotype was not observed (Fredlund et al 2013;Lindblad et al 2013 (Nielsen et al 2012). Our data add to a growing set of studies indicating a geographical partitioning of trichothecene types (chemotypes or genotypes) throughout Europe, with 3-ADON dominating in Northern Europe, whereas 15-ADON appears predominant in the Western and Southern Europe including the UK (Jennings et al 2004), Belgium (Audenaert et al 2009), Italy (Prodi et al 2009;Somma et al 2014), Luxembourg (Pasquali et al 2010), Poland (Stępień et al 2008), Hungary (Toth et al 2005), Germany (Talas et al 2011), and France (Boutigny et al 2014). …”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The 3- isolates belonging to population 2 were included in the analysis of aggressiveness, ten of these were included in the growth rate analysis c 17 3-ADON isolates were included in the analysis of aggressiveness, 16 of these were included in the growth rate analysis ADON chemotype also predominated among a small set of FGSC isolates from an earlier collection of Norwegian cereals (Langseth et al 1999(Langseth et al , 2001, and was found in oat and wheat samples collected between 2009 and 2011 in Sweden, whereas the 15-ADON chemotype was not observed (Fredlund et al 2013;Lindblad et al 2013 (Nielsen et al 2012). Our data add to a growing set of studies indicating a geographical partitioning of trichothecene types (chemotypes or genotypes) throughout Europe, with 3-ADON dominating in Northern Europe, whereas 15-ADON appears predominant in the Western and Southern Europe including the UK (Jennings et al 2004), Belgium (Audenaert et al 2009), Italy (Prodi et al 2009;Somma et al 2014), Luxembourg (Pasquali et al 2010), Poland (Stępień et al 2008), Hungary (Toth et al 2005), Germany (Talas et al 2011), and France (Boutigny et al 2014). …”
Section: Discussionsupporting
confidence: 64%
“…In addition, long distance dispersal of viable F. graminearum spores is possible (MaldonadoRamirez et al 2005;Schmale et al 2012). We speculate whether the increased prevalence of FGSC observed in several European countries (Chandelier et al 2011;Jennings et al 2004;Stępień et al 2008;Waalwijk et al 2003) including the Nordic countries (Bernhoft et al 2010;Fredlund et al 2008;Nielsen et al 2011;YliMattila 2010) may have facilitated the introduction of the 15-DON genotypes into new areas like Norway and Denmark. As such, the prevalence of 15-ADON genotypes and associated mycotoxin levels in Norwegian cereals should be monitored.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations